Bioterrorism threat: A review of microbial forensics source-tracing of some bioterrorism agents - Bobmanuel Chimaroke Echeonwu; Obinna O Nwankiti; Solomon C Chollom; Kayode A Olawuyi (Wolters Kluwer Medknow Publications, 2018)
Global perception and consciousness of the threat of bioterrorism seem to have diminished in recent past following achievements in decades of global fight against deadly infectious diseases such as plague and smallpox. However, with recent advancement in biotechnology and the arrival on the scene of amoral and rogue states as well as terrorist groups, there is a justifiably heightened global apprehension that bacteria, viruses, and toxicogenic fungi can be weaponized and used to cause great harm to humans and agricultural biodiversity. We now have on our hands the dilemma of dual-use of biotechnology. This review brings to the fore an aspect of microbial forensics - bioagent source-tracing (attribution) that is very key in mounting an appropriate response to the evident threat of bioterrorism. This article places a little more emphasis on the bioagent Yersinia pestis, and the technique of whole-genome sequence typing adjudged the most effective technique for building databases for bioterrorism-associated agents and public health important pathogens. The need for international sharing of data and databases of bio-agents is emphasized, as this would enable global applicability of bio-agent source-tracing in cases of bioterrorism.